Constructing Narratives of Loss and Damage : Framing, Experiences, and Governance in Tropical Fisheries through Blue Justice - N'guetta, Alicia ; 0000-0002-8693-2540 (Lund University, 2025)
Tropical fisheries are at the frontline of climate impacts and rising loss and damage. Yet, limited attention has been paid to fisheries, particularly "small-scale" fisheries, which play a vital role in sustaining livelihoods, ways of life, and well-being. With no consistent and sometimes contested definition, loss and damage refers to the negative impacts of climate change that were not addressed successfully by mitigation and adaptation. As a reality in everyday life, yet a topic of many competing interests in its construction, this thesis explores how loss and damage is framed, experienced and governed in tropical small-scale fisheries. Through an empirical investigation in Martinique (France), I first reflect on the framing of loss and damage for fisheries actors and its interplay with dominant framings of loss and damage. I then look into fishers' experiences and knowledge of loss and damage, as well as narratives across actors, to provide empirical evidence for an inclusive and justice-oriented governance in this area. I draw on critical constructivist theories to frame the study's boundaries and I use a Blue Justice lens to analyse situated knowledges, values, and hermeneutical injustices in fisheries. Four distinct but interlinked academic papers drawing on qualitative methods are included. Paper I reviews the framing of loss and damage in fisheries. Paper II empirically analyses fishers' situated knowledges of socio-ecological changes to inform loss and damage. Paper III explores the multidimensionality of loss and damage, reflecting on (in)tangible, non-finite and ambiguous, and disenfranchised grief dimensions. Finally, Paper IV proposes an equity framework for governing loss and damage in fisheries. The findings show that loss and damage has been constructed mainly through an economic and quantitative lens, contrasting with an understanding of loss and damage as multidimensional, relational, and complex in everyday life. Shaped by both historical climatic and non-climatic drivers, loss and damage is profoundly contextual and bound up with unresolved social justice matters. The findings reveal that experiences of environmental loss influence other forms of loss and damage. However, the ambiguous nature of these losses complicates the identification of temporalities and adaptation strategies, and has deep emotional implications. By advancing our understanding of the nature of loss and damage through the lived experiences of people (i.e. fishers), this thesis contributes to the theoretical understanding of loss and damage, with the aim of supporting increase social justice and a sustainable future.
Keywords: Climate Change; Fisheries; Justice; Governance; Marine; Coastal; loss and damage; Klimatförändringar; Fiske; Rättvisa; Styrning; Marin; kustnära; förluster och skador